Created snag characteristics and cavity-nesting bird associations in the CFIRP stands, McDonald-Dunn Research Forest, Corvallis, OR, USA, 2016 - Amy M. Barry; Joan C. Hagar; James W. Rivers (USGS Science Data Catalog, 2017)
Snags provide critical habitat for nearly one-third of wildlife species in forests of the Pacific Northwest, so historic declines in snags are thought to have had a strong impact on biodiversity. Resource managers often create snags to mitigate the scarcity of snags within managed forests, but information regarding the function and structure of created snags across long time periods (>20 years) is absent from the literature. Using snags that were created by topping mature Douglas-fir trees (Pseudotsuga menziesii) as part of the OSU College of Forestry Integrated Research Project, we measured characteristics of 731 snags and quantified foraging and breeding use of snags by birds 25-27 years after their creation. We also examined whether different harvest treatments (i.e., group selection, two-story, clearcut) and snag configurations (i.e., scattered and clustered) influenced snag characteristics or avian use for foraging and nesting. In addition, we conducted point count and call play-back surveys to calculate naive occupancy estimates for cavity-nesting bird species.